Exploring some Elements of Piracy in Selected Literary Works by Lord Byron - Sékou TOURÉ (Ziglôbitha, 2024)
Abstract: This research paper investigates and develops the persistence of piracy in some of Lord Byron’s literary works. The target works are basically narratives the poet had been told during his oriental voyages in Albany, Ottoman Empire, in Greece, etc… The Giaour, the Corsairs and the Bride of Abydos are all stories closely related to pirate activities all around the Mediterranean Sea. The objective of the study is therefore to account for some elements of piracy in selected works by Lord Byron. The sum total of all these are done within the theoretical context of socio-criticism. Since the study has used written documents as its primary instruments for the data collection, the qualitative methodology is therefore adopted in implementation of the study. The results of the study indicate that in the Corsairs, Conrad and his troops have assaulted upon Seyd’s harem. The pacha has contrived to defeat Conrad and his troops. Gulnare, the pacha’s favorite slave woman has successfully rescued Conrad and has taken him back to his homeland. In the Bride of Abydos, two young men have questioned their father’s authority, and subsequently have fled away to a grotto for refuge. Old Giaffir, their father, has sent troops to quell their sedition against social norms. In the Giaour, Giaour (the hero) has clashed with Hassan, the slave master, about one of his favorite slaves Leila. These three narratives echoed intense pirate activities relevant of the fifteenth century in the Mediterranean basin. Keywords: elopement, love, piracy, self-destruction, socio-criticism.